Model Emisi Gas Buangan Kendaraan Bermotor Akibat Aktivitas Transportasi (Studi Kasus: Terminal Pasar Bawah Ramayana Koita Bandar - Muziansyah, Devianti; Sulistyorini, Rahayu; Sebayang, Syukur (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2015)
Ramayana Underground Terminal of Bandar Lampung City is one of the largest contributorsexhaust emission levels, where the freight car transport activity is very high. Transportation is oneof the activities that contribute as a producer of motor vehicle exhaust emissions both gasolineand diesel.The aim of this study is to make model the relationship between vehicle exhaust emissions withtransport activity, to determine the factors that affect emissions, calculate emissions, and calculatethe emission losses in rupiah per year in Ramayana Underground Terminal of Bandar LampungCity.Relationship models obtained from the linear regression equation using SPSS 16 for dieselpassenger cars is Y = -19,401 + 0,684 X1 + 11,497 X2 +0,031 X3 and for gasoline passengercars is Y = 20,060 + 0,143 X1 + 0,421 X2 + 0,028 X3 and for motorcycles is Y = 9,049 + 0,082X1 + 0,921 X2 + 0,051 X3. Where the exhaust emissions value (Y), the age of the vehicle (X1),vehicle maintenance (X2) and the capacity of the machine (X3). Based on a survey and analysis ofthe emission load calculations and the cost of damages for Ramayana Underground Terminalworth Rp 63.492.632 / year.Keywords: Transportation, gasoline, diesel, exhaust emissions, SPSS 16